Wrapped in beauty : the Koelz collection of Kashmiri shawls - Beardsley, Grace, 1913-2003 (Anthropological papers (University of Michigan. Museum of Anthropology), 2005)
Accompanying CD-ROM contains ... "photographs of all the shawls in the accompanying book, plus an unpublished manuscript by Walter N. Koelz."--CD-ROM label